Control of the Rat Pineal Gland by Light Spectra - Cardinali, Daniel P. (1972)
Control of pineal hydroxyindole-O-methyl transferase (S-adenosylmethionine:N-acetylserotonin-O-methyl transferase; EC 2.1.1.4) by light spectra was determined by placing groups of rats previously housed in continuous darkness under one of seven light sources for 96 hr; rats were exposed to the same intensity of irradiation. Activity of the enzyme was lowest in rats maintained under green light (λ peak = 530 nm); blue and yellow light were somewhat less effective; red and ultraviolet light did not significantly lower the enzyme activity. The suppression of pineal hydroxyindole-O-methyl transferase by full-spectrum light sources could be correlated with the proportions of their spectral outputs in the blue-green-yellow range. These observations suggest that the retinal photopigment that mediates pineal responses to light in rats is rhodopsin or another compound with similar absorption properties.